2013
DOI: 10.1093/molbev/mst259
|View full text |Cite
|
Sign up to set email alerts
|

Cytonuclear Interactions and Relaxed Selection Accelerate Sequence Evolution in Organelle Ribosomes

Abstract: Many mitochondrial and plastid protein complexes contain subunits that are encoded in different genomes. In animals, nuclear-encoded mitochondrial proteins often exhibit rapid sequence evolution, which has been hypothesized to result from selection for mutations that compensate for changes in interacting subunits encoded in mutation-prone animal mitochondrial DNA. To test this hypothesis, we analyzed nuclear genes encoding cytosolic and organelle ribosomal proteins in flowering plants. The model angiosperm gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 82 publications
4
105
1
1
Order By: Relevance
“…First, if a demographic bottleneck had occurred, we would expect an excess of nonsynonymous divergence across all genes, but we did not observe this in the mtCLP genes or the randomly chosen nuclear genes. Previous studies in Silene also support the conclusion that the observed changes are not the result of genome-wide demographic effects; analysis of 140 cytosolic ribosomal proteins and seven mitochondrial-targeted complex II genes in S. conica and S. noctiflora did not show elevated d N /d S relative to other Silene species (Sloan et al 2014b;Havird et al 2015). Second, we observed elevated levels of nonsynonymous divergence across different timescales in our MK tests (Table 3 and Table S7) by using two different outgroups: S. latifolia (5.7 MY divergence time) and S. macrodonta (1.8 MY divergence time; Rautenberg et al 2012).…”
Section: Loss Of Plastid Heteromeric Accasesupporting
confidence: 63%
See 3 more Smart Citations
“…First, if a demographic bottleneck had occurred, we would expect an excess of nonsynonymous divergence across all genes, but we did not observe this in the mtCLP genes or the randomly chosen nuclear genes. Previous studies in Silene also support the conclusion that the observed changes are not the result of genome-wide demographic effects; analysis of 140 cytosolic ribosomal proteins and seven mitochondrial-targeted complex II genes in S. conica and S. noctiflora did not show elevated d N /d S relative to other Silene species (Sloan et al 2014b;Havird et al 2015). Second, we observed elevated levels of nonsynonymous divergence across different timescales in our MK tests (Table 3 and Table S7) by using two different outgroups: S. latifolia (5.7 MY divergence time) and S. macrodonta (1.8 MY divergence time; Rautenberg et al 2012).…”
Section: Loss Of Plastid Heteromeric Accasesupporting
confidence: 63%
“…In addition, recent studies showed correlated increases in d N /d S between nuclear-and plastidencoded subunits in ribosomal (Sloan et al 2014b;Weng et al 2016) and RNA polymerase complexes (Zhang et al 2015), providing further evidence for changes in selection pressures. However, these studies could not confidently distinguish between two alternative explanations for increased d N /d S , positive selection and relaxed purifying selection, which can be difficult to disentangle based on sequence divergence data alone.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Indeed, interactions between organellar genomes (mitochondria and plastids) and host genotypes appear to often affect host fitness (e.g., refs. [17][18][19][20].…”
mentioning
confidence: 99%